Actualization of Dana Punia in The Hindus Perception of Hindu Literature - Sujatindriasih, Ni Luh Putu; Sri Wati, Ni Putu; Arta Jiwa, Dewa Nyoman (Jayapangus Press, 2023)
Hinduism has teachings that guide its adherents to always be on the path of Dharma in this living life. Although these religious teachings are very antique, they still apply to their time. At some point in the Kaliyuga era, it was said that the function of Dana Punia (donation) was essential in spiritual life. Hindu scriptures teach that almsgiving can not only be done by giving tangible assets but can also be done by giving with an honest and sincere heart despite sacrificing feelings and giving goods in the form of body and soul. In addition, Dana Punia is defined as a gift to eliminate fear. Dana Punia must be done with sincere feelings and selflessness. This study aimed to discover how Dana Punia’s actualization in the Hindu’s perception of Hindu literature teachings. The method used in this study was library research and literature review. The results showed that almsgiving money could not only be done by giving treasures with certainty but could also be done by giving with an honest and sincere heart while giving up feelings and giving goods in the form of forms. Dana Punia was also referred to as a gift to ease worry or anxiety.